Asian Millennials' views on thermal baths – from medical to wellness service experiences. Issue 2 (1st September 2020) - Tang, Irini Lai Fun; Chan, Eric; Chew-Tan, Theresa; Wong Leung, Roberta
ABSTRACT: Thermal bath culture developed in Europe where bathers visited natural springs in Bath in England, Slovakia in Eastern Europe and Baden-Baden in Germany. Gradually, hot spring destinations were also developed in the United States and Canada and thereafter in Asian countries, including Japan and Korea. A few thermal bath resorts were established in Southern China in the 1980s, such as the Zhongshan Hot Spring Resort. However, daytime visitors and tourists have not paid special attention to these leisure activities, including millennial travellers. In this study, we explore how Asian millennials view thermal baths and whether they believe these baths should be developed in Mainland China given the scarcity of research knowledge about this area. During the COVID-19 pandemic, questions arose regarding how peoples' daily routines could include thermal bath therapies within their own cities and countries as travel became impossible. Given these circumstances, the Critical Incident Technique is used for over 500 random samples of millennial university students to recall their recent thermal bath experiences. Through content analysis, repeated keywords from findings summarize the students' concerns and whether thermal bath wellness service expereinces are feasible in Mainland China or Asia.